Retrospective Mid-Term Follow-Up of Posttraumatic and Iatrogenic Neurovascular Complications in Surgically Treated Paediatric Patients with Distal Humerus Fracture - Alexander Gutwerk; Peter Behrendt; Svenja Vetter; Leif Menzdorf; Edward Oates; Sebastian Jazra; Sebastian Lippross; Tim Klüter; Andreas Seekamp; Matthias Weuster (MDPI AG, 2022)
Background: The purpose of the study was to investigate and describe neurovascular complications and mid-term clinical outcomes of operatively managed fractures of the distal humerus in a paediatric population. Neurovascular injuries are common in these fractures, but reports about their implications for mid-term clinical outcomes is sparse. Methods: A single-centre retrospective study was conducted at a university teaching hospital investigating paediatric patients who underwent operative management of a distal humerus fracture between 2014 and 2018. Patient demographics, fracture classification, pre-, peri- and postoperative neurovascular complications were investigated. Mid-term follow up clinical examination and functional scoring using QuickDASH, the Broberg and Morrey Score (BMS), the Mayo Elbow Performance Score (MEPS) and the Numeric Rating Scale were performed. Results: A total of 84 patients were identified, of which 34 met the inclusion criteria and were available for follow-up clinical examination. The average time to follow-up was 150 weeks (1049.44 days ± 448.54). Ten primary traumatic neurovascular complications were identified, the majority of which involved the median nerve. Primary traumatic dissection of the brachial artery was recorded in three patients. Secondary iatrogenic nerve injury was documented in five patients after previously normal clinical examination. At follow-up, the average QuickDASH score was 3.0 ± 4.3, BMS was 98.6 ± 3.4 and MEPS was 97.1 ± 3.3 points. Conclusions: The mid-term clinical outcome following surgical management of distal humerus fractures is excellent. There is, however, a considerable frequency of both primary and secondary neurovascular complications, which must be considered when opting to treat these injuries surgically.